Researching Resistance : Public Education after Neoliberalism. - Huckaby, M. Francyne (Bloomfield : Myers Education Press, 2019)
"This book serves two vital functions. First, it explores, explicates, and encourages critical qualitative research that engages the arts and born-digital scholarship. Second, it offers options for understanding neoliberalism, revealing its impact on communities, and resisting it as ideology, practice, and law. The book delves into: strategies for engaging neoliberalism; the Black feminist cyborg theoretical assumptions and intentions of the ethnographic web-based film project; the research and arts-based methodology that walks the fault line between film and ethnography, and; the relationships between the researcher, the activist organizations, and the activism. While the book will focus on neoliberalism within the realm of public education, the implications extend to many other areas of public life."--
Homo Œcodnomicus, Schooling, & BlameFieldnotes: Houston; Section IV: Cyborg Writing; 8. Researcher | Researched; By Ruth Kravetz, Alpa Sridharan, Shilpa Sarang, and Anne Sung; 9. cyborg author; reluctant cyborg; Deciding to trust . . .; Reflections on academics . . .; Being part of student learning . . .; Validation for students & work ... ; Wishes and possibilities . . .; Suggestions for writing . . .; Section V: As We Weave; 10. Fairytales & Poets; After; References; Index
Print version record.
Includes bibliographical references (pages 189-203) and indexes.
eBooks on EBSCOhost
Keywords: Public schools -- United States; Neoliberalism -- United States; Education -- Aims and objectives -- United States; Écoles publiques -- États-Unis.; Néo-libéralisme -- États-Unis.; Education -- Aims and objectives; Neoliberalism; Public schools; United States